Prayer and Well-Being: Do Mindfulness, Optimism, Spirituality, and Social Support Mediate a Relationship Between Prayer and Well-Being in a Canadian-Muslim Population? - Albatnuni, Mawdah (Université d'Ottawa / University of Ottawa, 2020)
Research tells us that there is an effect of prayer on well-being. However, little is known about the mechanisms that underlie this relationship. In addition, much of the available data concerning prayer and well-being is based on Christians living in the United States, and our knowledge of how prayer and well-being are functionally interconnected in other faith groups, including Muslims, is sparse. The primary aim of this study was to understand how prayer impacts well-being in individuals of the Muslim faith. Specifically, four potential mediators of the relationship between prayer and well-being were examined; optimism, spirituality, mindfulness, and social support. These mediators were selected based on previous empirical work demonstrating the role these factors have in both religious practices and mental health. Optimism, spirituality, and social support are important mechanisms in the relationship between prayer and well-being in Christian samples, while mindfulness underlies the beneficial effects of contemplative practices on well-being in studies focused on Buddhist practices. In this study it is proposed that as a contemplative practice of the Abrahamic faith, Muslim prayer (salah) relates to well-being through the mediatory roles of optimism, spirituality, social support, and mindfulness. Participants (N=155) were recruited from local mosques, Muslim Student Associations of the University of Ottawa and Carleton University, local halal restaurants, and MuslimLink (an Ottawa-based Muslim newsletter). SurveyMonkey was used to gather information on participants’ prayer habits, and level of trait mindfulness, spirituality, optimism, social support, and subjective well-being. The data were analysed using a parallel multiple mediator model via the Monte Carlo confidence interval to test for the indirect effect of the mediator variables. Optimism and spirituality were both found to be mediators of the relationship between frequency of prayer and subjective well-being. While mindfulness correlated with both frequency of prayer and well-being, it did not mediate the relationship between the two. Social support correlated with frequency of prayer and not well-being and was not a mediator between the two variables. Psychological interventions that incorporate faith-based practices have been found to have greater effectiveness for religious patients. Understanding prayer and how it relates to well-being is important to implementing intervention and prevention strategies that are culturally informed thus better serving the Muslim population needs.
Keywords: Prayer; Muslim; Mediation; Spirituality; Optimism; Mindfulness; Well-being